Exposure to alcohol during adolescence exerts long-term effects on stress response and the adult brain stress circuits - Allen, Camryn D.; Grigoleit, Jan-Sebastian; Hong, Joonho; Bae, Sejin; Vaughan, Joan; Lee, Soon (Neuroscience, 2016)
•AIE blunts the young adult and adult corticosterone response to alcohol.•AIE blunts paraventricular nucleus Avp expression response to alcohol challenge.•AIE increases adult brain stem PNMT activation response to alcohol challenge. The hypothalamic–pituitary–adrenal (HPA) axis undergoes critical developments during adolescence. Therefore, stressors experienced during this period potentially have long-term effects on adult HPA axis function. We hypothesized that adolescent intermittent ethanol (AIE) exposure would affect adult HPA axis function, resulting in altered responses to an alcohol challenge in young adults or adults. To test these hypotheses, male rats were exposed to alcohol vapor for 6h per day from post-natal day (PND) 28–42, then acutely challenged with alcohol intragastrically (3.2–4.5g/kg) in young adults (PND 70) or adults (PND 90). Overall, we observed blunted HPA axis responses to an alcohol challenge due to AIE exposure. Specifically, AIE tended to inhibit the alcohol challenge-induced increase in plasma corticosterone (CORT) concentrations in young adult and adult rats. As well, AIE significantly blunted the alcohol challenge-induced arginine vasopressin (Avp) mRNA expression in the paraventricular nucleus (PVN) of the hypothalamus of adult rats. Results of the present study are similar to what we have previously shown, that these changes in PVN responsiveness may result from AIE-induced alterations in adrenergic neurons in brain stem regions C1–C3 known to project to the PVN. AIE elevated the number of colocalized c-fos/phenylethanolamine N-methyltransferase (PNMT)-positive cell bodies in the C1 region of adult rats. Together, these data suggest that AIE exposure produces alterations in male HPA axis responsiveness to administration of an acute alcohol challenge that may be long-lasting.